Sistema para detección y conteo vehicular aplicando técnicas de visión artificial. - Sisalima Ortega, Fabricio Roberto (2018)
The present work of certification consists in the development of a software of counting vehicular applying techniques of vision by computer. This application greatly benefits the transit area for decision making based on the data collected by the software, demonstrating with this the feasibility today of the development of image processing software for applications in real environments. It presents the possible algorithms to be used and the choice of the best alternative for the solution of this particular problem. For the development of the titling work, research methods were used to identify the problem of the project and provide an optimal solution to it, techniques were applied such as the interview for the collection of information with the client and the bibliography to support the theoretical basis of the project. project and finally the XP development methodology that allowed to keep an order during the software development process. The counting software was developed with the C ++ language using the Qt framework, the computer vision library selected was Opencv itself, which has the implementations of the algorithms to be used in the vehicle detection and counting process. The use of the methods, techniques and tools previously exposed allowed to fulfill the objectives set out in the project, resulting in the construction of a software that meets the needs requested by the client.